2005
DOI: 10.1110/ps.051481105
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear transfer of perchloric acid–soluble protein by endoplasmic reticulum stressors

Abstract: Perchloric acid-soluble protein (PSP) is highly conserved during evolution from bacteria to mammals. Although PSP has been recognized as an inhibitor of translation and proliferation in vitro, its precise biological role has not yet been elucidated. Since we previously found similar distributions for PSP and the endoplasmic reticulum (ER) and Golgi complex, the intracellular distribution of PSP was analyzed in more detail. Immunofluorescence studies indicated that PSP co-localized with the ER and Golgi complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…They are considered multifunctional, as reported in different organisms. Furthermore, they have different biological functions [ 11 , 12 , 13 ], and many of them are related to RNA mechanisms [ 14 ]. We determined that the Tv-PSP1 trimer structure, where the interaction with RNA is positively charged, agrees with previous findings for a protein from E. coli with a positively charged, trimeric conformation of the ST0811 surface, thus suggesting that this may favor RNA molecule interactions [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are considered multifunctional, as reported in different organisms. Furthermore, they have different biological functions [ 11 , 12 , 13 ], and many of them are related to RNA mechanisms [ 14 ]. We determined that the Tv-PSP1 trimer structure, where the interaction with RNA is positively charged, agrees with previous findings for a protein from E. coli with a positively charged, trimeric conformation of the ST0811 surface, thus suggesting that this may favor RNA molecule interactions [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…The L-PSP protein family possesses different biological functions [ 11 , 12 , 13 ] and possible activity as a ribonuclease [ 14 , 15 , 16 ]. A perchloric-acid-soluble protein (PSP) named Tv-PSP1 was previously reported in T. vaginalis [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another enzyme identified among TBPs, ribonuclease UK114 is expressed in kidney and liver. Expression of this ribonuclease decreases during transformation of the cells and it is transferred to the nucleus in response to stress (Kanouchi et al, 2005). Several proteins involved in regulation of transcription were also found among the TBPs.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous results showed that PSP exists in the cytosol, endoplasmic reticulum (ER), or Golgi complex, but not in the nuclei in proliferating culture cells. 4,11) ER stresses induce a dramatic increase in the localization of PSP to the nuclei and in the induction of PSP expression. 11) We speculate that cell proliferation was suppressed under the ER-stress condition by induction of PSP expression and accumulation of PSP in the nuclei.…”
mentioning
confidence: 99%
“…4,11) ER stresses induce a dramatic increase in the localization of PSP to the nuclei and in the induction of PSP expression. 11) We speculate that cell proliferation was suppressed under the ER-stress condition by induction of PSP expression and accumulation of PSP in the nuclei. In the case of liver regeneration, PSP perhaps needs to be down-regulated and then deleted from the nuclei to enter from the G 0 phase into the proliferation phase cells.…”
mentioning
confidence: 99%